Using Communicative Action Theory to Analyse Relationships Between Supervisors and Phd Students in a Technical University in Sweden - Christie, Michael; Garrote Jurado, Ramon (Högre utbildning, 2013)
In this paper the authors use the theory of communicative action (Habermas, 1984-6) to analyse problematic relationships that can occur between supervisors and PhD students, between co-supervisors and between the students themselves. In a situation where power is distributed unequally, instrumental and strategic action on the part of either party can complicate and disturb efficacious relationships. We use Flanagan’s critical incident technique (Flanagan, 1954) to analyse twenty-five incidents that are told from a supervisor perspective and twentyfive from a PhD student perspective. The analysis reveals that a large proportion of incidents involved power struggles. Other categories include lack of professional or emotional support and poor communication. Rational dialogue based on Habermasian principles might have avoided many of these problems. The analysis concludes with some practical suggestions as to how the use of communicative action theory and critical incident technique can improve supervision, supervision training and the PhD process.